Designing gRNAs targeting oil palm phytoene desaturase (EgPDS) gene and construction of vectors for oil palm CRISPR/Cas9 study - Jamaludin, Norfaezah; Bahariah, Bohari; Shaharuddin, Noor Azmi; Chai, Ling Ho; Abdul Rasid, Omar; Ahmad Parveez, Ghulam Kadir; Abdul Masani, Mat Yunus (Malaysian Palm Oil Board, 2022)
The CRISPR/Cas9 system is a precise and versatile genetic tool used to induce site-specific manipulation in the targeted gene. This study elaborates on the strategy to select the gRNAs targeting the oil palm phytoene desaturase (EgPDS) gene, which complements CRISPR-GE and sequence analysis. Sixty-one gRNAs were selected from 167 gRNA candidates generated by the CRISPR-GE tool. These gRNA candidates were further analysed to meet the specific criteria, including the guanine (G) and cytosine (C) content of 35%-60% and the presence of preferable gRNA features. From 61 gRNAs, seven gRNAs were selected, which represent three different parts of the EgPDS gene in the genome. The efficiency of each gRNA candidate to cause cleavage on the target gene was confirmed by in vitro cleavage analysis. All seven gRNA candidates were then cloned into the pYLsgRNA-OsU6 cassette before being incorporated seamlessly into the final transformation vector, pYLCRISPR/Cas9P35S-H, via Gibson assembly. Three CRISPR/Cas9 transformation vectors targeting the EgPDS gene, namely pYLEgPDS1-35S-H, pYLEgPDS2-35S-H and pYLEgPDS3-35S-H, were successfully constructed. These constructs will be transformed into oil palm protoplasts via polyethylene glycol (PEG)- mediated transformation and subsequently into oil palm embryogenic calli via biolistic and Agrobacteriummediated transformation to determine the efficacy of the multiplex CRISPR/Cas9 system in oil palm genome.